Blurring Boundaries. - Salomon, Stefan (BRILL, 2017)
In Blurring Boundaries: Human Security and Forced Migration scholars from law and social sciences offer a fresh view on the major issues of forced migration through the lens of human security. Although much scholarship engages with forced migration and human security independently, they have hardly been weaved together in a comprehensive manner. The contributions cover the issues of refugee law, maritime migration, human smuggling and trafficking and environmental migration. Blurring Boundaries critically engages boundaries produced in the law with the main ideas of human security, thus providing a much-needed novel vocabulary for a critical discourse in forced migration studies.